Stochastic and Deterministic Fault Detection for Randomized Gossip Algorithms - Silvestre, Daniel (2018)
Compute the average of the initial states in finite-time. Guarantee fault detection and bounds on the maximum possible deviation from an attack. Incorporate the transmissions stochastic information in the fault detection mechanism